A comparative analysis of firm co-location behaviour in the Detroit metropolitan area. Issue 3 (16th March 2018) - Mack, Elizabeth A.; Credit, Kevin; Suandi, Matthew
Abstract: Multinational enterprises (MNEs) now exhibit knowledge-seeking behaviours which are critical to maintain or gain a competitive advantage. Emerging work about the interaction between MNEs, space and place also highlights the need for finer scale research to understand the strategy and knowledge exchange of MNEs, which remains limited to this point. To address this need for fine-grained analyses of firm co-location behaviour, this paper uses point-level data to test hypotheses about the co-location behaviour of three types of manufacturing firms in the Detroit metropolitan area. Variations in this behaviour highlight that foreign rather than domestic firms may be the primary source of knowledge spillovers, which speaks to the internationalisation of manufacturing activity in the region over time. New domestic standalone ventures appear to have been crowded out from cluster activities, suggesting a policy opportunity to integrate new standalone ventures into collaborative ventures with other firms in the region.